Education and Its Importance in the Context of Bangladesh Education System - Noor, Masud Al (Advances in Social Sciences Research Journal, 2017)
Education is the back bone of the nation. Without proper education it cannot be possible to make a wise nation. Bangladesh education system is not competitive in terms of compare with international level. Lack of unified curriculum and skilled teacher is the main factor to develop education sector and political illness is another factor to improve those system. It is time to identify the problems and find out the remedy. With a strong education system a highly qualified generation may emerge to lead Bangladesh in realizing the dreams and goals of the nation. The paper presents a significant analysis of education system of Bangladesh.